Higher integrity of the motor and visual pathways in long-term video game players - Zhang, Yang; Du, Guijin; Yang, Yongxin; Qin, Wen; Li, Xiaodong; Zhang, Quan (Frontiers in Human Neuroscience, 2015)
Long term video game players (VGPs) have been reported to exhibit superior visual and motor skills compared with non-video-game controls (NVGCs). However, the neural basis underlying the enhanced behavioral performance remains largely unknown. To clarify this issue, the present study compared the whiter matter integrity within the corticospinal tracts (CST), the superior longitudinal fasciculus (SLF), the inferior longitudinal fasciculus (ILF), and the inferior fronto-occipital fasciculus (IFOF) between the VGPs and the NVGCs using diffusion tensor imaging (DTI). Compared with the NVGCs, voxel-wise comparisons revealed significantly higher fractional anisotropy (FA) value in some regions within the left CST, left SLF, bilateral ILF and IFOF in VGPs. Furthermore, higher FA value at the cerebral peduncle level of the left CST predicted faster response in visual attention task. These results suggested that the higher WM integrity in the motor and higher-tier visual pathways is associated with long-term video-game playing, which may contribute to the understanding of the neuromechanism of the effect of video game play on the motor and visual process performance.